Optimizing the Performance of Unit III Satreskrim to Increase Disclosure of Corruption Crimes in the Jurisdiction of the Semarang Polrestabes (Advances in Police Science Research Journal, 2024)
This final project aims to analyze the organizational resources, cooperation, and management processes used by Unit III of the Criminal Investigation Department to optimize its performance in uncovering corruption crimes in the jurisdiction of the Semarang Metropolitan Police. In this final project, the author used a qualitative descriptive method with a case study approach and collected data through interviews, observation, and documentation studies at Unit III of the Criminal Investigation Department of Semarang Metropolitan Police. This final project covers three main issues, namely organizational resources, cooperation, and management processes. Organizational resources include Man, Money, Material, and Method. Cooperation includes communication, coordination, and collaboration stages both internally and externally. Meanwhile, the management process includes planning, organizing, implementing, and monitoring. In this final project, the author found that factors such as limited personnel in terms of quality and quantity, suboptimal utilization of budget, inadequate facilities and equipment, ineffective and inefficient methods, lack of coordination with relevant agencies and the public, and suboptimal organizational management can affect the performance of Unit III of the Criminal Investigation Department. From the analysis results, it can be concluded that problem-solving steps are needed to optimize the performance of the Criminal Investigation Department by improving the factors that affect its performance. Therefore, to optimize the performance of the Criminal Investigation Department, the author recommends several efforts to improve the quality and quantity of personnel, increase the utilization of the budget, improve facilities and equipment, create efficient and effective methods, increase coordination with relevant agencies and the public, and formulate new Standard Operating Procedure to help optimize the performance of Unit III of the Criminal Investigation Department. Thus, Unit III of the Criminal Investigation Department can contribute more significantly in handling corruption crimes in the jurisdiction of the Semarang Metropolitan Police.
Keywords: Corruption crime, Polrestabes Semarang, Optimization